Teacher Education, Well-Being and a Sense of Belonging - Ragoonaden, Karen Olivia; Cherkowski, Sabre; Kutsyuruba, Ben; Walker, Keith; Claypool, Tim; Basch, Jodi; Godden, Lorraine (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
This article draws from a Canadian project examining the holistic dimensions of well-being in teacher education programs. In keeping with calls to action in research and in the practice of teacher education, conceptualizations offering a wider view of well-being—beyond physical, mental, and emotional health—guided the inquiry. This study presents findings from a questionnaire disseminated to students in three teacher education programs in Western Canada. The results indicated that the teacher education programs addressed the vocational, social, intellectual, and cultural dimensions of well-being. Dimensions relating to emotional, physical, spiritual, and financial well-being were not consistently addressed. Of note was the financial precarity impacting the well-being of a majority of respondents. Since a sense of belonging was identified as an important indicator of well-being, especially for students who identify as Black, Indigenous, and people of colour (BIPOC), these findings may guide teacher education programs in adopting productive ways to navigate the distinct realities of students in a post-pandemic society.